Pola Interaksi Antar-lembaga dan Reformasi Tata Kelola Keamanan Maritim Indonesia: Bakamla RI - Adi Wibawa; Muhammad Ridha Iswardhana; Hidayat Chusnul Chotimah (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
Maritime security is an essential aspect for an archipelagic country like Indonesia. In addition, as stated by President Joko Widodo, maritime defense forces are also one of the five pillars in realizing Indonesia as the